Analisa Tegangan dan Deformasi Pada Desain Kursi Menggunakan Finite Element Method Dengan Variasi Pembebanan - Didik Sugiono; Suprapto Suprapto; Yopan Rahmad Aldori; Supardi Supardi (Infotekmesin, 2025)
The manufacturing process is an activity of processing raw materials into products to increase added value. One of these products is chair furniture; to reduce errors and failures in its manufacture, it is necessary to do prototype model experiments first. This research conducts a simulation study and analysis of the chair design on stress, deformation and safety factor using the Finite Element Method approach with the help of ANSYS ADPL 18.0 static structural software where the chair design is made of 304 stainless steel, aluminum-T6, HCP 30 polymer foam in one chair structure by simulating several static load loading scenarios, boundary conditions, and even distribution on the surface of the chair. The simulation results show that the highest maximum stress distribution (von misses stress) is 3.5 Mpa at a pressure of 175 kg.f, for the lowest value of 1.5 Mpa at a pressure of 5 Kg.f and a deformation (displacement) of 0.145x10Ë‰4 mm occurs at a pressure of 175 Kg.f, while the lowest deformation value of 0.621x10Ë‰5 occurs at a pressure of 75 Kg.f, This is due to the loading increasing along with the applied pressure force, but still in the minimum safety factor standard position for static loads, so as not to damage the geometric structure.